Peran Guru Dalam Meningkatkan Minat Baca Siswa Di Sekolah Dasar Desa Teep Trans - Ndolu, Sumardi W.; Kadore, Alvrin; Dunggio, Alfando T.; Darenoh, Clara M. (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to describe the role of teachers in enhancing students’ reading interest at the Elementary School of Teep Trans Village, South Minahasa Regency. The research employed a qualitative approach with a case study method, using observations, interviews, and documentation as data collection techniques. Data analysis followed the model proposed by Miles, Huberman, and Saldaña. The findings show that teachers strive to improve students’ reading interest through shared reading activities, the use of picture-story media, literacy routines, and motivational reinforcement. These strategies were effective in increasing students’ engagement and enthusiasm for reading activities. However, several challenges were identified, including limited book availability, low parental support for reading activities at home, and the basic reading difficulties experienced by some students. Teachers responded to these issues by providing individual guidance and diversifying literacy activities. The study concludes that teachers play a crucial role in fostering students’ reading interest, although optimal outcomes require adequate school facilities and active parental involvement.